2005
DOI: 10.1177/00222194050380010401
|View full text |Cite
|
Sign up to set email alerts
|

Social Information Processing and Emotional Understanding in Children with LD

Abstract: The present study aimed to comprehensively examine social cognition processes in children with and without learning disabilities (LD), focusing on social information processing (SIP) and complex emotional understanding capabilities such as understanding complex, mixed, and hidden emotions. Participants were 50 children with LD (age range 9.4-12.7; 35 boys, 15 girls) and 50 children without LD matched on grade, age, and gender. Children analyzed 4 social vignettes using Dodge's SIP model and completed 2 emotion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
111
2
9

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 117 publications
(132 citation statements)
references
References 43 publications
10
111
2
9
Order By: Relevance
“…Children-The first scale, the Friendship Observation Scale (FOS) (Bauminger et al 2005), was an interactional coding system designed to assess minute-by-minute and global evaluations of manifestations of friendship in the target child, including behaviors, verbalizations, and affects identified as indicators of friendship by previous research (e.g., Asher et al 1996). The FOS was adapted from the procedure used by Siperstein et al (1997) to assess friendship manifestations during a construction game among children with and without learning disabilities.…”
Section: Observed Friendship Manifestations In Targetmentioning
confidence: 99%
See 2 more Smart Citations
“…Children-The first scale, the Friendship Observation Scale (FOS) (Bauminger et al 2005), was an interactional coding system designed to assess minute-by-minute and global evaluations of manifestations of friendship in the target child, including behaviors, verbalizations, and affects identified as indicators of friendship by previous research (e.g., Asher et al 1996). The FOS was adapted from the procedure used by Siperstein et al (1997) to assess friendship manifestations during a construction game among children with and without learning disabilities.…”
Section: Observed Friendship Manifestations In Targetmentioning
confidence: 99%
“…Emotional Recognition-The Affective Matching Measure (Bauminger et al 2005;adaptation of Feshbach 1993) assessed children's ability to recognize emotions from their social context. The child was shown 12 different pictures depicting social scenarios of eight different emotions: One picture for each of the four basic emotions (happiness, sadness, anger, and fear) and two different pictures for each of the four complex emotions (embarrassment, loneliness, guilt, and pride).…”
Section: Measures: Semi-structured Tasksmentioning
confidence: 99%
See 1 more Smart Citation
“…Seven papers were identified that matched the search criteria and inclusion/exclusion criteria. Bauminger et al, (2005) Six of the papers do not give a definition of social cognition per se, although some do provide definitions for the specific areas of social cognition they are researching. Leffert, Siperstein & Millikan (2000) define two areas of social cognition: social perception and social strategy generation.…”
Section: Social Cognition and Children With Intellectual Disabilitiesmentioning
confidence: 99%
“…Four of the papers (Bauminger et al, 2005;Gomez & Hazeldine, 1996;Leffert & Siperstein, 1996;Tur-Kaspa, 2004) primary aim was to investigate social information processing, and all cite the model proposed by Dodge (1986;Crick & Dodge, 1994). This model involves six steps: 1) encoding social cues from the environment; 2) forming a mental representation and interpretation of the cues; 3) searching for possible behavioural responses; 4) deciding on a response from those generated; 5) enacting the selected response; 6) enactment-including monitoring the effects of behaviour and regulating it.…”
Section: Social Cognition and Children With Intellectual Disabilitiesmentioning
confidence: 99%